2009
DOI: 10.1080/09670260802578534
|View full text |Cite
|
Sign up to set email alerts
|

Azadinium spinosumgen. et sp. nov. (Dinophyceae) identified as a primary producer of azaspiracid toxins

Abstract: Azaspiracids (AZAs) are a group of lipophilic marine biotoxins associated with human incidents of shellfish poisoning. During a research cruise to the North Sea, we analysed size-fractionated plankton for AZA by mass spectrometry and successfully isolated an AZA-producing dinoflagellate from the east coast of Scotland. As shown previously, an axenic culture of this dinoflagellate produces AZA 1, AZA 2 and an isomer of AZA 2. Here we give a taxonomic description of this new taxon Azadinium spinosum gen. et sp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
226
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 251 publications
(240 citation statements)
references
References 45 publications
13
226
1
Order By: Relevance
“…Characters of these two orders were also shared by species in the genera of Azadinium Elbra¨chter and Tillmann, Amphidoma Stein and Bysmatrum Faust and Steidinger (Faust & Steidinger 1998;Tillmann et al 2009;Tillmann et al 2012). Despite morphological similarities, Bysmatrum is phylogenetically distant from Vulcanodinium (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Characters of these two orders were also shared by species in the genera of Azadinium Elbra¨chter and Tillmann, Amphidoma Stein and Bysmatrum Faust and Steidinger (Faust & Steidinger 1998;Tillmann et al 2009;Tillmann et al 2012). Despite morphological similarities, Bysmatrum is phylogenetically distant from Vulcanodinium (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Morphology, light-and electron microscopy A number of small dinoflagellate cells (as identified at low magnification by shape and swimming patterns) were observed in wells with sediment samples after about 1½ weeks of incubation. Among those, Azadinium-like cells as defined by their conspicuous swimming pattern (see accompanying video in Tillmann et al, 2009) were isolated as single cells, and from these 10 clonal cultures of Azadinium were obtained. Light-and electron microscopy of all isolates confirmed that they all were identical in terms of morphology and that they all represented the species Azadinium poporum.…”
Section: Azaspiracidsmentioning
confidence: 99%
“…However, the toxins, and thus presumably the causative organism(s), are widely distributed, mainly in western Europe (Satake et al, 1998;James et al, 2002;Bran˜a Magdalena et al, 2003;Vale et al, 2008), but also on the coast of Morocco (Taleb et al, 2006) and northern Chile (Alvarez et al, 2010). Subsequent to the erroneous attribution of AZA toxins to the heterotrophic marine dinoflagellate Protoperidinium crassipes as the primary source organism (James et al, 2003a), rather than merely as a toxin vector, the culprit for AZA production was recently unambiguously identified and described as a novel species within a newly created genus Azadinium Elbra¨chter & Tillmann Tillmann et al, 2009). The toxigenic type species, a small photosynthetic dinoflagellate, described as Azadinium spinosum Elbra¨chter & Tillmann, was isolated off the Scottish east coast, but was also detected by molecular methods in samples from the Danish coast , indicating a wide distribution in the North Sea.…”
Section: Introductionmentioning
confidence: 99%